2021
DOI: 10.3390/nu13041302
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Calorie Restriction on Health Span and Insulin Resistance: Classic Calorie Restriction Diet vs. Ketosis-Inducing Diet

Abstract: As the incidence of Chronic Non-Communicable Diseases (CNCDs) increases, preventive approaches become more crucial. In this review, calorie restriction (CR) effects on human beings were evaluated, comparing the benefits and risks of different CR diets: classic CR vs. ketosis-inducing diets, including intermittent fasting (IF), classic ketogenic diet (CKD), fasting mimicking diet (FMD), very-low-calorie ketogenic Diet (VLCKD) and Spanish ketogenic Mediterranean diet (SKMD). Special emphasis on insulin resistanc… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(35 citation statements)
references
References 131 publications
(190 reference statements)
1
23
0
1
Order By: Relevance
“…1 In a meta-analysis and systematic review of cardiovascular disease mortality and cancer incidence in vegetarians, it was reported that vegetarians had a significantly lower ischemic heart disease mortality (−29%) and overall cancer incidence (−18%) than non-vegetarians. 1 Various other dietary practices have reported associated health benefits, for example, a vegan diet, 2 a ketogenic diet, 3 a calorie restriction diet 4 and a Mediterranean diet. 5 One particular dietary custom that appears to provide long-term health benefits is consumption of up to 5 servings per day of fruit and vegetables.…”
Section: Introductionmentioning
confidence: 99%
“…1 In a meta-analysis and systematic review of cardiovascular disease mortality and cancer incidence in vegetarians, it was reported that vegetarians had a significantly lower ischemic heart disease mortality (−29%) and overall cancer incidence (−18%) than non-vegetarians. 1 Various other dietary practices have reported associated health benefits, for example, a vegan diet, 2 a ketogenic diet, 3 a calorie restriction diet 4 and a Mediterranean diet. 5 One particular dietary custom that appears to provide long-term health benefits is consumption of up to 5 servings per day of fruit and vegetables.…”
Section: Introductionmentioning
confidence: 99%
“…Controlling dietary intake has been hypothesized to relieve physical and mental burdens associated with obesity ( 24 ). However, in recent years, an increasing number of studies has shown that CR provides patients with numerous other benefits in addition to weight loss ( 25 , 26 ). Choi et al ( 27 ) stated that CR allows the body to eliminate harmful cells while generating healthy new cells, therefore alleviating multiple sclerosis symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…High-fat diets, such as the ketogenic diet, have proven to have many benefits. For example, the ketogenic diet was effective in treating epilepsy and Type 2 Diabetes in young and middle-aged adults (Napoleão et al, 2021). While ketosis-inducing diets can improve metabolic and other syndromes, they can have negative effects on the circadian clock.…”
Section: Nutritionmentioning
confidence: 99%